1984
DOI: 10.1136/bjo.68.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Retinal branch vein occlusion: a study of argon laser photocoagulation in the treatment of macular oedema.

Abstract: City Road, London EC] V2PD SUMMARY A control trial is reported which demonstrates that treatment with argon laser photocoagulation to certain patients with macular oedema following a branch vein occlusion does not alter significantly their visual prognosis. It confirms that patients with an intact perifoveal capillary arcade have a better prognosis than those with a broken arcade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
2
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 9 publications
1
45
2
1
Order By: Relevance
“…[2][3][4][5] It has also been suggested that even in I-BRVO patients with intact foveal avascular zones, improvement with treatment may not be significantly different from that seen in the natural history of I-BRVO patients as a group. [6][7][8] Clearly, the patients in this study benefited from treatment, most remarkably Cases 1 and 3 where ischaemia extended into the foveal avascular zone.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] It has also been suggested that even in I-BRVO patients with intact foveal avascular zones, improvement with treatment may not be significantly different from that seen in the natural history of I-BRVO patients as a group. [6][7][8] Clearly, the patients in this study benefited from treatment, most remarkably Cases 1 and 3 where ischaemia extended into the foveal avascular zone.…”
Section: Commentmentioning
confidence: 99%
“…[1][2][3] Macular oedema is the major cause of vision loss in these patients and it is still unclear when or indeed if argon laser treatment should be used to improve visual acuity when BRVO is associated with ischaemia (I-BRVO). [2][3][4] Some I-BRVO patients benefit from treatment, but important aspects of the treatment regimen remain unclear such as which patients to treat, when to treat, and how much treatment is needed.…”
mentioning
confidence: 99%
“…10,13,28 poor visual outcome correlates with increased foveal avascular zone (FaZ) 29 or disruption of perifoveal capillaries seen in fluorescein angiograms. [30][31][32] Similarly in BRvO patients treated with grid laser, those with intact perifoveal capillaries have a better visual prognosis than those with perifoveal capillary disruption. 31 Nonperfusion is a significant baseline factor for development of disc or retinal neovascularization in patients with BRvO with the highest risk at ≥5.5 disc areas.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…[30][31][32] Similarly in BRvO patients treated with grid laser, those with intact perifoveal capillaries have a better visual prognosis than those with perifoveal capillary disruption. 31 Nonperfusion is a significant baseline factor for development of disc or retinal neovascularization in patients with BRvO with the highest risk at ≥5.5 disc areas. 33 the use of optical coherence tomography (Oct), particularly spectral domain Oct (SD-Oct), has brought attention to a correlation between visual acuity and the visualization of inner segment/outer segment (iS/ OS) and/or external limiting membrane (elm) at the fovea.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…To date, no proven effective treatment has been shown in large randomized studies. There are various treatment modalities for retinal vein occlusion including systemic treatments such as hemodilution, anticoagulation therapy and fibrinolysis; intravitreal agents such as steroids, anti-vascular endothelial growth factor agents (VEGF), and dexamethasone implant; laser photocoagulation treatment, fibrinolytic treatment modalities such as intravitreal administration of t-PA, direct injection of tissue plasminogen activator (t-PA) into the lumen of a retinal vein via retinal vein cannulation, super selective ophthalmic artery catheterisation, and surgical approaches such as pars plana vitrectomy (PPV), arteriovenous sheathotomy, radial optic neurotomy (RON), chorioretinal venous anastomosis [5][6][7][8][9][10][11] . The aim of this review is to describe the outcomes of fibrinolytic and surgical treatment modalities for RVO.…”
Section: Introductionmentioning
confidence: 99%